ChemInform Abstract: Transformation of Benzo[b]thiophene‐2, 3‐diones to Functionalized Diaryldisulfides. Issue 46 (24th October 2013) - Pardasani, Ramchand T.; Singh, Saurabh; George, Johnson; Joshi, Rahul; Sundar, T. Vaidyanathan
Abstract via nucleophilic ring opening with Et2NH